UPAYA PENYELESAIAN KREDIT BERMASALAH PADA LEMBAGA PERBANKAN - Muhammad Yasid; Risha Ramayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
Impaired credit can cause the disturbance of the continuity of business activities circulation in a Bank and in the end it can cause the disturbance of banking financial liquidity. When a Bank liquidity decreases, it can decrease its credibility level that it can affect people/customer/investor’s trust who will invest in the Bank. Based on this background, the researchers were interested in the problem that encouraged them to do a research entitled “The Efforts on the Recovery of Loss Credit in Banking Institution” This research applied Constructivism Paradigm with descriptive and prescriptive as the nature. The source of data was library study. The data analysis method used by the researchers was descriptive qualitative. The results of the study showed that in the efforts of the recovery of loss credit, there were three (3) main activities done: through the parties’ agreement as the best way for both parties to recover it, the saving of the loss credit and/or the recovery through legal way. The purpose of recovering the loss credit was to save the bank funds invested in the form of loss credit by paying attention to the debtor’s business condition which still had good prospect. It was hoped that the saving could recover the quality of the credit from “loss” collectability to “doubtful”. From “doubtful” to “bad” , from ‘substandard” to “pass”.